Релейная защита на оперативном переменном токе - Мельник Павел Максимович (Гостехиздат УССР, 1953)
Экземпляры: КХ (20241112) / Инвентарный номер: 149157 / Сис.шифр: 621.31 / Авт.знак: М 48 / ГРНТИ: 44 / ББК: 31